Neo-Bibliometric Analysis of research thesis in the Academic and Professional School of Psychology of UNMSM - Quintana Peña, Alberto (2006)
It is carried out a study neo-bibliometrico of the pre-grade theses sustained in the EAP of Psychology of the Unversidad Nacional Mayor de San Marcos during the period 2000-2005, carrying out an itemized analysis of the corpus of data with the Format of Evaluation of the Reports of Investigation FORI, to respond to the query How the investigations are made to opt the I title professional in the EAP of Psychology of the UNMSM? The database this way obtained it was processed with the ×2 statistical program SPSS 0.12, arriving to the following summations: In the sample predominate investigate thesis basicfeasible, opposite to «case’s study» and «essay». The specific topics usually are «psychological processes, about the cognition area, academic achievement and sexual behavior». The egresados that you/they investigated the topic of the basic psychological processes with a cognitive-behavioral focus has developed studies Frequently they were used like references sources of information The frequently studied population the adolescents conform (students of secondary and university students), Limean and of middle class.